Attitudes and practices of students towards HIV/AIDS voluntary counselling and testing at the University of Limpopo, South Africa. - Jali, N. M.; Tladi, F. M.; Malema, R. N.; Thopola, M. K. (My University, 2014)
The purpose of this study was to determine the attitudes and practices of students towards voluntary counselling and testing (VCT) for HIV/AIDS at the University of Limpopo. A qualitative, exploratory, descriptive and contextual research design was used to describe the attitudes and practices of students towards VCT at the University of Limpopo, Limpopo province. The population consists of all students who visit the University of Limpopo health centre to meet their health needs including voluntary counselling and testing for HIV/ AIDS. A non- probability purposive sampling method was used to obtain a sample size of fifteen (15) participants. Semi-structured interviews were used to collect data until data saturation was reached. Data were analyzed using Tesch’s open coding method of qualitative data analysis. The following themes emerged from the data analysis: knowledge of VCT, importance of VCT and attitudes of health professionals. Fear of stigmatization was one of the most important barriers to VCT uptake. The study also revealed that health care professionals exhibited non-caring behaviours towards participants who sought VCT services. It was recommended that more emphasis should be placed on sensitizing students about HIV/AIDS so as to erase the stigma attached to HIV/AIDS VCT.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:1 (June), 2014, pp. 1-14.
Keywords: HIV/AIDS; Voluntary counselling; Voluntary testing; AIDS (Disease) -- South Africa